Targeting Mitochondrial Integrity as a New Senolytic Strategy - Vacurova, Eliska; Vlachova, Edita; Stursa, Jan; Bohacova, Klara; Havrlantova, Tereza; Skop, Vojtech; Kasperova, Barbora Judita; Werner, Lukas; Neuzil, Jiri; Haluzik, Martin; Hubackova, Sona Stemberkova (Aging and disease, 2025)
Aging, characterized by accumulation of senescent cells, is a driving factor of various age-related diseases. These conditions pose significant health risks globally due to their increasing prevalence and serious complications. Reduction of senescent cells therefore represents a promising strategy promoting healthy aging. Here we demonstrate that targeting tamoxifen to mitochondria via triphenyl and tricyclohexyl phosphine selectively eliminates senescent cells. Our findings show a complex effect of mitochondrially targeted tamoxifen on mitochondrial function and integrity of senescent cells, including inhibition of oxidative phosphorylation and activity of respiratory complex IV. These changes result in activation of ferroptosis as the major mode of cell death, which results in rejuvenation of tissues. Targeting mitochondria of senescent cells represents a general senolytic strategy and may extend the healthspan and improve the quality of life in aging populations.